IMPLEMENTASI PENDIDIKAN KARAKTER DALAM PEMBELAJARAN FIQIH DI MTS NEGERI 3 HST - Ubaidillah Ubaidillah (CV. Adiba Aisha Amira, 2023)
This study aims to determine the implementation of character education learning in the field of Fiqh studies at MTs Negeri 3 HST, to find out the supporting factors and inhibiting factors for the implementation of character education in the field of Fiqh studies. This research was conducted at MTs Negeri 3 HST which had implemented character education with the research subjects being the principal, deputy student affairs, vice curriculum teacher, fiqh teacher and students using descriptive qualitative research methods, interview and observation data collection techniques. The results of the study illustrate that the implementation of character education in fiqh subjects includes the planning, implementation stages. The implementation of character education in fiqh learning has supporting factors and inhibiting factors including the awareness of students to change and the inhibiting factor is the lack of parental control in the implementation of character education when students are outside the school environment